Stress-Related Disorders 2022
DOI: 10.5772/intechopen.102947
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Mental Health

Abstract: The COVID-19 crept in silently and subsequently spread at a rapid pace ultimately progressing into a pandemic with a high rate of morbidity, mortality, loss of income and sustained social isolation for billions of people. This sudden human tragedy required heavy adjustment and was difficult to adapt quickly as we humans are gregarious in nature and always need social connect in our lives especially during a crisis. History has shown that mental health impact of pandemics outlasts the physical impact. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…While researchers have analysed the the district level covid infection and fatalities [33, 34], as far as we know, our study is the first one to provide a comprehensive analysis of covid vaccination rates at the district level across the various phases of covid vaccination and the various demographic, socio-economic and health factors associated with the observed vaccination rates. Most existing research studies that have analysed the regional variation in the observed covid vaccination rates in India, research has been mostly limited to the heterogeneity in vaccine rates at the state level or a particular state or district and for early phases of vaccination [35, 36, 37, 38]. Our research makes important contributions to the field of public health research by improving our understanding of factors that are associated with covid vaccination rates in India and in providing directions for future research.…”
Section: Introductionmentioning
confidence: 99%
“…While researchers have analysed the the district level covid infection and fatalities [33, 34], as far as we know, our study is the first one to provide a comprehensive analysis of covid vaccination rates at the district level across the various phases of covid vaccination and the various demographic, socio-economic and health factors associated with the observed vaccination rates. Most existing research studies that have analysed the regional variation in the observed covid vaccination rates in India, research has been mostly limited to the heterogeneity in vaccine rates at the state level or a particular state or district and for early phases of vaccination [35, 36, 37, 38]. Our research makes important contributions to the field of public health research by improving our understanding of factors that are associated with covid vaccination rates in India and in providing directions for future research.…”
Section: Introductionmentioning
confidence: 99%